2022
DOI: 10.3390/microorganisms10122373
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Dynamics of the Gut Microbiota in Rice Fishes at Different Developmental Stages in Rice-Fish Coculture Systems

Abstract: The rice-fish system (RFS), a traditional coculture farming model, was selected as a “globally important agricultural heritage system.” Host-associated microbiota play important roles in development, metabolism, physiology, and immune function. However, studies on the gut microbiota of aquatic animals in the RFS are scarce, especially the lack of baseline knowledge of the dynamics of gut microbial communities in rice fish during different developmental stages. In this study, we characterized the microbial comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 104 publications
2
4
0
Order By: Relevance
“…4C) that CCE and CCY are similar to WE in terms of OTU level and genus classi cation, and can cluster together rst, which also indicates that in the very early stage of carp development, especially before feeding. The water environment has a great in uence on its ora, which is also consistent with the reports of many kinds of sh [41] [29] [42].…”
Section: Discussionsupporting
confidence: 85%
“…4C) that CCE and CCY are similar to WE in terms of OTU level and genus classi cation, and can cluster together rst, which also indicates that in the very early stage of carp development, especially before feeding. The water environment has a great in uence on its ora, which is also consistent with the reports of many kinds of sh [41] [29] [42].…”
Section: Discussionsupporting
confidence: 85%
“…The findings of this study reveal that Chinese alligators maintain a consistent core microbiota throughout their growth stages. The diversity of the gut microbiome, as measured by the α diversity index, shows minimal variation, and no significant differences, which aligns with research conducted on carp and zebrafish (Stephens et al., 2016; Tao et al., 2022). It is worth noting that the α diversity index reaches its highest point at 8Y and reaches its lowest point at 4Y.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the Pearson correlation analysis revealed that the abundance of Verrucomicrobiota and unclassified_ f_Rhodobacteraceae had a positive correlation with WGR, and the abundance of Firmicutes and Verrucomicrobiota had a positive correlation with SGR. Previous studies have shown that Firmicutes break down carbohydrates and degrade plant cell wall components to produce short-chain fatty acids, which provide nutrients for the host [36]. Furthermore, some Firmicutes have the ability to boost host immunity by upregulating immune genes expression [37].…”
Section: Discussionmentioning
confidence: 99%